Penerapan Kurikulum Berbasis Karakter di SD Islam Budi Mulia Padang - Fikra Aulya Irhas; Fetri Yeni J (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2019)
This study aims to determine the application of the curriculum at Budi Mulia Padang Islamic Elementary School, starting from the applied curriculum, learning planning, implementation of learning, and evaluation. This study uses descriptive research with a qualitative approach. Informants in this study were principals, representatives, teachers, and students. Data collection techniques used were observation, interviews, and documentation. Data were analyzed using interactive analysis models, namely data reduction, data display, and conclusion. The validity of the data test technique uses triangulation. The results of the study show that the curriculum used by Budi Mulia Padang Elementary School is a National curriculum, namely the 2013 Curriculum and Education Unit Level Curriculum, and the foundation curriculum, namely a character-based curriculum with a full day school system. Learning planning is carried out by designing syllabus and lesson plans by the teacher as a reference in carrying out classroom learning, and designing classroom management so that the classroom atmosphere is comfortable and enjoyable. The implementation of learning in the classroom is carried out using methods and media that vary according to the theme being studied by inserting character values. Character cultivation is also carried out outside learning activities, namely through routine activities and school culture as well as self-development / extracurricular activities. Evaluation is carried out by assessing aspects of knowledge, attitudes, and skills of students according to the theme with the format stated in the teacher's lesson plan.